Application of Principal Component Analysis in distinguishing three species of 'jernang' (Daemonorops spp.). Issue 1 (November 2021) - Andini, R; Yanti, L A; Rasnovi, S; Sulaiman, M I; Moulana, R; Muzaifa, M; Putri, S N; Widiastuti, A
Abstract: The province of Aceh at the northern tip of Sumatra has a total area of 5, 75 million hectares. Its forest resources are considerably extensive as 60% of its total land area is still considered as 'forest area'. Non-Timber Forest Products (NTFP) are defined as any wild plant and animal products harvested from forests, e.g., ' jernang ' or dragon blood ( Daemonorops spp.). It is classified as one of the valuable NTFP's harvested from the forests in Aceh. Its morphological features resemble that of rattan ( Calamus spp.), both of which belong to Aracaceae. The red resin of Daemonorops spp. is highly valued in Chinese medicine and possesses anti-inflammatory, anti-tumor, and anti-hemostatic properties. Almost 112 species of Daemonorops spp. exist. However, only 10% produces the red resin. Daemonorops draco, D. mattanensis, D. didymophylla are considered to have significant economic values. Over the past decade, a farmer living in central and western Aceh has cultivated dragon blood plants in small farms and sold the seedlings. In this study, the morphological variations of dragon blood (N=11) from Kuta Panang in central Aceh were assessed, and the Principal Component Analyses (PCA) were applied in order to distinguish the three species. Up to 92% of total variations were significantly explained with PC1, while the remaining were explained with PC2. Among the three species measured with PCA, Daemonorops draco or known as super ' jernang ', appeared to have more distinctive morphological characteristics, e.g., fruit-, and stem diameter, as well as a number of fruit per trunk. These characteristics would contribute to better yield and field performance.